Next Generation Sequencing - Advances, Applications and Challenges 2016
DOI: 10.5772/61610
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Next-generation Sequencing Data in Virology - Opportunities and Challenges

Abstract: Viruses are the most abundant and the smallest organisms, which are relatively simple to sequence. Genome sequence data of viruses for individual species to populations outnumber that of other species. Although this offers an opportunity to study viral diversity at varying levels of taxonomic hierarchy, it also poses challenges for systematic and structured organization of data and its downstream processing. Extensive computational analyses using a number of algorithms and programs have opened exciting opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 121 publications
0
6
0
4
Order By: Relevance
“…deep sequencing) that we were unable to accomplish in our work. As reviewed in Quiñones-Mateu et al (2014) [42], this approach is being increasingly used in diagnostic laboratories, given the significance of VAF in human clinical virology [43]. It would be of great interest to implement this practice on a routine basis also for animal viruses, where the selection at viral population level of signatures implicated in immune evasion and host jump are particularly relevant [44–48].…”
Section: Discussionmentioning
confidence: 99%
“…deep sequencing) that we were unable to accomplish in our work. As reviewed in Quiñones-Mateu et al (2014) [42], this approach is being increasingly used in diagnostic laboratories, given the significance of VAF in human clinical virology [43]. It would be of great interest to implement this practice on a routine basis also for animal viruses, where the selection at viral population level of signatures implicated in immune evasion and host jump are particularly relevant [44–48].…”
Section: Discussionmentioning
confidence: 99%
“…Unfolding evolutionary dynamics of viruses enhances the understanding of quasispecies diversity and the involvement of mutations in drug resistance and host switching, enabling the genotypic and phenotypic characterization of viruses (Kasibhatla et al, 2016). Zhang et al (2011), with the aid of deep and whole-genome sequencing, reported Grapevine vein clearing virus (DNA virus) in six grapevine cultivars linked with the vein-clearing symptom for the first time in Indiana, Missouri, and Illinois, indicating its widespread distribution in the Midwest of the United States.…”
Section: Next-generation Sequencing Technologies As Go-to Tool For Plant Virologymentioning
confidence: 99%
“…While HIV pol gene sequencing largely serves the needs for HIVDR genotyping, such sequencing data is often also applied in molecular epidemiology, such as cluster analysis. Thus far, NGS-based cluster analyses are largely based upon (1) NGS consensus sequences that simply mimic SS sequences; (2) reconstructed viral variants using quasispecies reconstruction tools that often perform poorly on HIV NGS data [ 56 , 57 ].…”
Section: Figurementioning
confidence: 99%